The Relationship Between Nutritional Status and the Incidence of Dysmenorrhea in Adolescent Girls: A Frequency Analysis Based on Nutritional Status Categories - Lintang Dwi Ariyanty; Sunarto Sunarto; Astuti Setiyani; Hery Sumasto (Knowledge Dynamics, 2024)
Background: Dysmenorrhea is a common complaint that occurs during menstruation. The main research problem is that dysmenorrhea is often experienced by young women with high cases. The results of preliminary studies show that adolescents with poor nutritional status or malnutrition have a 50% risk of experiencing dysmenorrhea. This study aims to analyze the relationship between nutritional status and the incidence of dysmenorrhea in adolescent girls. Methods: This type of research is observational analytic with a cross-sectional design. The population is all students in class VII MTs. Negeri 2 Magetan, totaling 225 students. The sample size was 144 students, calculated using the Slovin formula. The sampling technique is simple random sampling using a lottery. The independent variable in this study is nutritional status, and the dependent variable is dysmenorrhea. Instruments for measuring height use a height-measuring device, and instruments for measuring body weight use a weight scale. The instrument for measuring dysmenorrhea uses a questionnaire. Nutritional status data was collected by measuring body weight and height, while dysmenorrhea data was collected by filling out questionnaires. Analyze the data descriptively, and test the hypothesis using the Chi-Square statistical test. Results: The results of the study obtained a picture of 144 female students studied, half of whom had abnormal nutritional status (54.9%), and dysmenorrhea (54.2%). The prevalence ratio of exposure to abnormal nutritional status to the incidence of dysmenorrhea is 0.91. Then at 95% significance, there is a relationship between nutritional status and dysmenorrhea. Conclusion: This study concludes that there is a relationship between nutritional status and the incidence of dysmenorrhea in young women at MTs. Negeri 2 Magetan and the prevalence ratio of dysmenorrhea from exposure to abnormal nutritional status was 50.7%. Comprehensive nutritional education and early health intervention are recommended to prevent and reduce the risk of dysmenorrhea.